2010
DOI: 10.1021/nn901884d
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Temperature Distribution and Cancer Cell Death in Response to Extracellular Hyperthermia Induced by Gold Nanorods

Abstract: Plasmonic nanoparticles have shown promise in hyperthermic cancer therapy, both in vitro and in vivo. Previous reports have described hyperthermic ablation using targeted and non-targeted nanoparticles internalized by cancer cells, but most reports do not describe a theoretical analysis for determining optimal parameters. The focus of the current research was first to evaluate the spatiotemporal temperature distribution and cell death induced by extracellular hyperthermia in which gold nanorods (GNRs) were mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(171 citation statements)
references
References 61 publications
8
162
0
1
Order By: Relevance
“…Nevertheless, many of these models, even if they are targeted toward specific tumor mass, may face challenges in confining heat production at the very local levels; studies show that during the photothermal treatments of the cells using the nanoparticles, the temperature of the entire field is raised by a significant amount. [48][49][50][51] This could raise serious concerns about damage upon nearby, non-targeted tissue as the entire field is being affected. Our method tries to overcome this drawback by promoting target-specific attachment of the nanoparticle products to the tumor: This had led to dramatic reduction in overall heat generation of the field (Figure 5), while producing enough thermal energy at proximity to the target to induce sufficient damage on the tumor while minimizing temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many of these models, even if they are targeted toward specific tumor mass, may face challenges in confining heat production at the very local levels; studies show that during the photothermal treatments of the cells using the nanoparticles, the temperature of the entire field is raised by a significant amount. [48][49][50][51] This could raise serious concerns about damage upon nearby, non-targeted tissue as the entire field is being affected. Our method tries to overcome this drawback by promoting target-specific attachment of the nanoparticle products to the tumor: This had led to dramatic reduction in overall heat generation of the field (Figure 5), while producing enough thermal energy at proximity to the target to induce sufficient damage on the tumor while minimizing temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, several PhT-NPs have been proposed including metallic nanoparticles, semiconductor nanocrystals, graphene nanocrystals, and carbon nanotubes. [19][20][21][22][23][24][25][26][27][28] Few previous works have also reported that certain rare earth doped nano-crystals (RE-NPs) could be also used as PhT-NPs, although this possibility has not been demonstrated yet in biocompatible colloidal solutions. 29 Certain RE-NPs have demonstrated to be highly efficient luminescence probes under excitation with Near Infrared (NIR) radiation within the biological windows.…”
mentioning
confidence: 99%
“…Local heating zones with higher temperature near the AuNR will likely persist, however, over the full course of our photoinduced thermal activation period. 20,21 Accordingly, even from very early heating times, the proteins adsorbed to the AuNR surface may experience very different solution temperatures than free proteins during photoinduced thermal treatments. Because of the thermal gradient in solution that results from photoinduced heating of the AuNRs, any given protein (e.g., apolipoproteins) may have different conformations depending on whether the proteins are adsorbed on the AuNR surface or are located a few hundred nanometers from the surface of laser activated nanorods.…”
mentioning
confidence: 99%